PENGARUH CELEBRITY ENDORSEMENT DAN E-WOM TERHADAP KEPUTUSAN PEMBELIAN PENGGUNA SHOPEE - Irvan Rolyesh Situmorang (Fakultas Ekonomi Universitas Negeri Medan, 2024)
The aim of this study is to ascertain and evaluate the relative and concurrent effects of E-WOM and celebrity endorsements on East Bantan District Shopee customers' purchase decisions. This study employs a quantitative methodology with a Likert scale for measurement. Since the exact population of this study is unknown, sampling is done using the Hair formula, which multiplies the number of indicators by five for the minimum and ten for the maximum. Users of Shopee in the East Bantan District completed surveys that yielded the research findings. Multiple linear regression is the type of regression analysis employed. Shopee consumers in the East Bantan Subdistrict make less purchases as a result of the outcomes of the first half test, which focused on celebrity endorsements. The outcome of evaluating the second hypothesis, which states that East Bantan District Shopee users' purchase decisions are positively impacted by E-WOM. Concurrent test findings demonstrated that E-WOM and celebrity endorsements positively impacted East Bantan District Shopee users' purchase decisions. The coefficient of determination revealed that E-WOM and celebrity endorsements had a 57.5% influence, with other factors not included in this study accounting for the remaining 42.5%